2022
DOI: 10.1111/jar.13059
|View full text |Cite
|
Sign up to set email alerts
|

Self‐advocates with Down syndrome research the lived experiences of COVID‐19 lockdowns in Aotearoa New Zealand

Abstract: Background Individuals with Down syndrome are particularly vulnerable to COVID‐19 because they are recognised as significantly immunocompromised. Yet their voices regarding their lived experiences of pandemic lockdowns have not been sought or heard. Aim This study aims to describe the lived experiences of people with Down syndrome during the pandemic lockdowns in Aotearoa New Zealand to add evidence in order to inform systemic advocacy. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…For example, several participants’ exploration of remote work opportunities appears to have been driven by day program closures, or the limitations of remote day‐time services. Further, although persons with ID have reported the limitations of using technology to maintain social relationships (Puyaltó et al, 2022), we found that several participants were empowered by technology to access remote work opportunities, consistent with findings by Spassiani et al (2023) and Vaccarino et al (2023) regarding social activities. Further, while the literature has largely correlated service disruptions with negative outcomes (e.g., Lunsky et al, 2022), we found that disruptions in pre‐existing, under‐inclusive adult disability service models prompted group home residents with ID to seek competitive employment or more independent living arrangements.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…For example, several participants’ exploration of remote work opportunities appears to have been driven by day program closures, or the limitations of remote day‐time services. Further, although persons with ID have reported the limitations of using technology to maintain social relationships (Puyaltó et al, 2022), we found that several participants were empowered by technology to access remote work opportunities, consistent with findings by Spassiani et al (2023) and Vaccarino et al (2023) regarding social activities. Further, while the literature has largely correlated service disruptions with negative outcomes (e.g., Lunsky et al, 2022), we found that disruptions in pre‐existing, under‐inclusive adult disability service models prompted group home residents with ID to seek competitive employment or more independent living arrangements.…”
Section: Discussionsupporting
confidence: 90%
“…Participants also demonstrated resilience by making positive changes amid pandemic-related challenges. Participants' feelings of isolation echo those reported by persons with ID not living in group homes (Vaccarino et al, 2023;Lake et al, 2021;Kim et al, 2021;Embregts et al, 2022), but appear to be exacerbated by group home residents' unique experiences of frequent lockdowns and staffingrelated community access limitations, as found by Puyalt o et al ( 2022). However, such feelings have not previously been linked to the disproportionate effects of these restrictions on group home residents with mobility impairments, which may parallel the compounded effects of restrictions faced by persons with both ID and visual impairments found by Honingh et al (2021).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations